The Influence of Social Media Marketing, Brand Awareness, and Brand Image on the Intention to Purchase Subsidized Housing: Pengaruh Social Media Marketing, Brand Awareness dan Brand Image Terhadap Niat Beli Rumah Subsidi - Prashesarb, Albino; Mahrinasari, Mahrinasari; Roslina, Roslina (Academia Open, 2026)
General Background: Social media marketing has become an essential strategy for increasing consumer engagement and purchase intention in the property sector. Specific Background: Property developers increasingly utilize Instagram-based marketing to promote subsidized housing and expand consumer reach through digital communication. Knowledge Gap: Limited studies have simultaneously examined the mediating roles of brand awareness and brand image in the relationship between social media marketing and subsidized housing purchase intention using the Stimulus–Organism–Response (SOR) framework. Aims: This study aimed to examine the relationships between social media marketing, brand awareness, brand image, and purchase intention for subsidized housing, including the mediating roles of brand awareness and brand image. Results: A quantitative correlational approach was employed using purposive sampling of Instagram followers, and the data were analyzed with SEM-PLS. The findings revealed that social media marketing positively and significantly affects brand awareness, brand image, and purchase intention. Furthermore, brand awareness and brand image positively and significantly affect purchase intention and successfully mediate the relationship between social media marketing and purchase intention. Novelty: This study integrates the SOR framework with the dual mediating roles of brand awareness and brand image to explain subsidized housing purchase intention in digital property marketing. Implications: The findings provide practical guidance for property developers to prioritize social media strategies that strengthen brand awareness and brand image to encourage consumer purchase intention. Highlights: Social media marketing significantly increased consumer brand recognition and perception. Brand awareness and brand image jointly mediated purchase intention. The proposed SEM-PLS model demonstrated substantial predictive capability. Keywords: Social Media, Intention, Brand